From legal affirmation to degrading anthropization of the Louzeiro’s bush: a socio-environmental analyses considering the SNUC law (Research, Society and Development, 2021)
Taking into consideration the Louzeiro’s bush, green area situated in the city area of Campina Grande – Paraíba, as an location which requires proper regulation and preservation, this work aims to highlight the current environmental challenges in this place, considering as a management parameter the SNUC law - Brazilian legislation that deals with Conservation Units. For this purpose, proceeds with exploratory and explanatory research, based on on-the-spot visits, data collection and a theoretical discussion about its adequacy to the to the legal order.  despite the existence of local legislation assuring the area a especial protection, considered in permanent preservation since the 1990s, there is not enough monitoring or implementing  of public policies  which inhibit the  main problems that increasingly degrade the environment as deforestation, irregular deposit of solid waste on the surface, vegetation suppression, extraction of sand  and the hunting of wild animals. This concern is based on the premise of the need to create a Conservation Unit, with the main object of preservation of nature and local natural resources, diagnosing the degradation of the area and the symbiotic relationship between the involved population. A process where all the parties involved becomes able to understand its importance to participate and improve conservation values, ruled by the well-being of the population, environmental education, participative management and sustainable development.